Assessment of the perception and understanding of the performance management system at the Department of Planning, Monitoring and Evaluation (DPME) - Pumane, Nokuthula (Stellenbosch : Stellenbosch University, 2020)
Thesis (MPA)--Stellenbosch University, 2020.